Modifiable risk factors for the development and severe course of diverticular disease: a review - Niderla, Natalia; Klohsek, Jakub (Journal of Education, Health and Sport, 2024)
Diverticulosis is a common condition of the bowel, particularly affecting the sigmoid colon with age-dependent increase in prevalence. While often asymptomatic and discovered incidentally during colonoscopies or imaging, some patients experience symptoms like left lower abdominal pain, bloating, and irregular bowel habits. When symptoms arise, it is termed diverticular disease (DD). Approximately 10% of diverticulosis cases progress to diverticulitis, which involves inflammation and can lead to complications like abscesses, perforation, or obstruction. In the U.S., acute diverticulitis accounts for 200,000 hospitalizations annually, costing about 2.2 billion in healthcare. The purpose of this paper is to review the current understanding of modifiable risk factors associated with the development and progression of diverticular disease